A history and philosophy of sport and physical education : from ancient civilizations to the modern world / Robert A Mechikoff - Mechikoff, Robert A
Takes students and scholars on a journey through time to understand the role that history and philosophy have played in shaping the course of sport and physical education in Western and selected non-Western civilizations, from Mesoamerica and Ancient Greece to the 2008 Olympic Games.